Exploring Certain Generalization of Arithmetical Functions - Kumar, Nand Kishor; Yadav, Dipendra Prasad; Pokhrel, Chudamani (Patan Prospective Journal, 2023)
This article introduces a few generalized arithmetical functions and focuses on a few specific instances of these arithmetic functions. This study of certain generalizations of arithmetical functions supplements our understanding of number theory and its applications. By spreading the domain, range, or definition of traditional arithmetical functions, mathematicians unexposed new insights into the structure of integers and their relationships with other mathematical objects. Moreover, the applications of these generalizations span across various fields of mathematics, highlighting their significance and relevance in modern mathematical research. Continued exploration of these generalizations promises further discoveries and advancements in the field of number theory and beyond.